Application of the quantum learning model in increasing adolescent happiness - Neni Elvira. Z; Firman Firman; Netrawati Netrawati (Counseling and Humanities Review, 2021)
Period teenager is period which urgent within range life, because is period something period transition, a time of change, a troubled age, a moment where individual look for identity, age which raises Fright, period which no realistic, and as threshold adulthood. Based on the stages of its development, adolescence is called a transitional period because it is experiencing physiological development, emotional development and social development which will cause fear, anxiety and even self-doubt. Happiness depends on how young people keep themselves in a condition to make the best use of our energy. Teenagers should feel happy at school and learning with teachers in class. Teacher BK / Counselor is wrong one educator which role in help students overcome obstacles or problems and develop potency which owned student in school including student happiness. One learning model that can increase student happiness in class is the quantum learning model. the Quantum learning model seeks to maximize all the elements contained in learning including all the potential and abilities that exist in students. This is intended to make the learning carried out by the teacher maximal and students also absorb the material presented maximally. The current research is descriptive qualitative with a literature study that seeks to provide an overview of the application of the Quantum learning model to increase adolescent happiness. This paper presents the problem of adolescent happiness at school, steps to apply the Quantum learning model and increase adolescent happiness at school. This research uses literature study / literature study, by reviewing several research results, articles, books and case studies that occur in the field.